Exercitiul 1. x-2(x-3)la adoua =(x+1)(3-2x)
2. 1-x=2x-(x-3)ori x+(x-4)la adoua
Răspunsuri la întrebare
Răspuns de
1
1.[tex]x-2(x^{2}-6x+9)=3x-2x^{2}+3-2x
x-2x^{2}+12x-18=x-2x^{2}+3
12x=21
x=21supra 12 [/tex]
2.[tex]1-x=2x-x^{2}+3x+x^{2}-8x+16 2x=15 x=15supra2[/tex]
2.[tex]1-x=2x-x^{2}+3x+x^{2}-8x+16 2x=15 x=15supra2[/tex]
Alte întrebări interesante
Limba română,
9 ani în urmă
Engleza,
9 ani în urmă
Matematică,
9 ani în urmă
Engleza,
10 ani în urmă
Fizică,
10 ani în urmă
Limba română,
10 ani în urmă